Diverse Fate of an Enigmatic Structure: 200 Years of Meckel’s Cartilage - Svandova, Eva; Anthwal, Neal; Tucker, Abigail S.; Matalova, Eva (Frontiers in Cell and Developmental Biology, 2020)
Meckel’s cartilage was first described by the German anatomist Johann Friedrich Meckel the Younger in 1820 from his analysis of human embryos. Two hundred years after its discovery this paper follows the development and largely transient nature of the mammalian Meckel’s cartilage, and its role in jaw development. Meckel’s cartilage acts as a jaw support during early development, and a template for the later forming jaw bones. In mammals, its anterior domain links the two arms of the dentary together at the symphysis while the posterior domain ossifies to form two of the three ear ossicles of the middle ear. In between, Meckel’s cartilage transforms to a ligament or disappears, subsumed by the growing dentary bone. Several human syndromes have been linked, directly or indirectly, to abnormal Meckel’s cartilage formation. Herein, the evolution, development and fate of the cartilage and its impact on jaw development is mapped. The review focuses on developmental and cellular processes that shed light on the mechanisms behind the different fates of this cartilage, examining the control of Meckel’s cartilage patterning, initiation and maturation. Importantly, human disorders and mouse models with disrupted Meckel’s cartilage development are highlighted, in order to understand how changes in this cartilage impact on later development of the dentary and the craniofacial complex as a whole. Finally, the relative roles of tissue interactions, apoptosis, autophagy, macrophages and clast cells in the removal process are discussed. Meckel’s cartilage is a unique and enigmatic structure, the development and function of which is starting to be understood but many interesting questions still remain.